ESP proposal for teaching business english oriented to flower sellers selling to english speaking buyers - Cerón Varela, Luis Alberto (2015)
Flower export has transcended beyond Ecuador‟s borders. This has created the necessity for the sales departments from flower exporters to master the English language, specifically business English oriented to flower sellers selling their products to English speaking buyers. This dissertation proposes to put together a course of English for specific purposes (ESP) that suits the needs of a group of flower sellers. Therefore, a situational and a needs analysis were performed in the field using digital surveys to learn about specific functions of the sales group. Once the information has been retrieved, an analysis of the language functions from the sales group was carried on. The result of these observations is a curriculum proposal, which has to be accepted for implementation by the company‟s management. Optimizing the sales group‟s time is crucial, so they will receive classes through videoconferences. The proposed course encloses a placement test (annex 3) to find out the potential students‟ English level. Also, it contains real elements the sales group use in their daily activities, like e-mails, buying orders, payment instructions (annex 4 to 6). Finally, this research concluded that the needs analysis is crucial to identify the language functions that are necessary to communicate with English speaking buyers. As a result, the course contains activities that will help the B1 students to improve their linguistic abilities aimed to flower selling.